The American political debate about the project to annex Texas and the legality of declaring war on Mexico (1844-1848) (Journal of the College of Basic Education, 2022)
This research deals with the historical roots of the issue of annexing Texas to the United States of America, the broad political controversy that accompanied the process of annexing it in Congress and the American public opinion, its impact on the presidential election race of 1844 between the Democratic Party and the Liberal Party, and the reasons that led to the outbreak of the American-Mexican War in 1846 And the political debate that arose about the decision of the US administration to declare war on Mexico in the corridors of the American political parties, the Congress, and the American public opinion, and the activity of the Democratic Party and the Liberal Party in defending their differing positions on that war.